Effect of novel polysiloxane functionalized poly(AMPS-co-CEA) membranes for base recovery from alkaline waste solutions via diffusion dialysis. Issue 115 (5th November 2015) - Mondal, Abhishek N.; Zheng, Chunlei; Cheng, Congliang; Hossain, Md. Masem; Khan, Muhammad Imran; Yao, Zilu; Wu, Liang; Xu, Tongwen
Abstract : The corresponding poly(AMPS- co -CEA) based membrane which showed high base permeability and proper separation factor in alkali recovery via DD process. Abstract : In the modern arena of separation science and technology, cation exchange membrane (CEM) based diffusion dialysis (DD) has attracted remarkable attention due to its unique ion transport phenomena during applications for base recovery. In this manuscript, for the first time we reveal novel disodium 4-formylbenzene-1, 3-disulfonate modified polysiloxane (FSP) induced poly(AMPS- co -CEA) based CEMs with polyvinyl alcohol (PVA) as a binder and tetraethoxysilane (TEOS) acting as a crosslinker for base recovery via diffusion dialysis. Synthesis of poly(AMPS- co -CEA) involved classical free radical polymerization with azobisisobutyronitrile (AIBN) acting as an initiator. By regulating the dosage of FSP in the membrane matrix, the physiochemical as well as the electrochemical properties of the prepared membranes can be modified. The prepared membranes were investigated comprehensively in terms of water uptake ( W R ), ion exchange capacity (IEC) along with thermo-mechanical measurements like DMA and TGA. The effect of FSP was discussed in brief to correlate the base recovery behaviour of the prepared membranes. The prepared CEMs have water uptakes ( W R ) in the range 204.0–248.7%, ion exchange capacities (IEC) between 0.58 and 0.76 mmol g −1, tensile strengths (TS) between 9.3 and 15.9 MPa as well as elongations at break ( E b ) of 125.6–236.7%. At 25 °C, the dialysis coefficient ( U OH ) values appeared as high as 0.0078–0.0112 m h −1 and the separation factors ( S ) ranged from 10.32 to 14.19. The membranes described in this manuscript could be a promising contender for base recovery via diffusion dialysis.